Analisis pengaruh sektor pertanian dan sektor perdagangan terhadap produk domestik regional bruto Kabupaten Magelang - Wahyuningtias, Agesti Duwi (Journal of Economics Research and Policy Studies, 2021)
Gross regional domestic product as a measuring tool for the success of economic development has a significant influence in planning to increase the potential income. Magelang regency is one of them, which has a sector of agriculture and trade that has not been optimized, including the direction of economic policies that are often inconsistent. This study aims to determine the effect of the agricultural sector and the trade sector on the gross regional domestic product of the Magelang Regency. This research is quantitative type research with multiple linear regression analysis methods. Using secondary data published by BPS Magelang Regency 2010-2017. Based on the research results, it is found that simultaneously the agricultural sector and the trade sector influence GRDP, while partially that affects, namely the trade sector, while the agricultural sector has no.